Memperkuat Solidaritas Melalui Pemasaran Digital di Pengajian Ibu-Ibu Masjid Babussalam, Kubu Raya, Kalimantan Barat - Syahbudi; Ria Safaria; Almiyah Damayanti; Shufi At-Tazkia; Ahmad Arif Ramadhan; Adi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This research aims to strengthen solidarity through digital marketing among women's Islamic study groups at Babussalam Mosque, Kubu Raya, West Kalimantan. The study employs a Community Based Research (CBR) model involving 26 active members who operate micro-businesses. Data collection methods included community assessment, participatory planning, and collaborative evaluation. The research results demonstrate that digital marketing training significantly enhanced members' capabilities in utilizing social media platforms (Lynk.id, TikTok, Shopee, Facebook, Instagram) for product promotion. Furthermore, economic solidarity was strengthened through collaborative promotion strategies, mutual support networks, and shared marketing activities. The impact includes expanded consumer reach, increased sales orders, and enhanced self-confidence among members in marketing their products. This study concludes that the CBR model effectively bridges academic knowledge with community needs, transforming religious study groups into spaces for women's economic empowerment through digital technology adoption.